2016
DOI: 10.3389/fpsyg.2016.01831
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Restoration Can Depend on Stimulus-Source Attribution: A Challenge for the Evolutionary Account?

Abstract: Visiting or viewing nature environments can have restorative psychological effects, while exposure to the built environment typically has less positive effects. A classic view is that this difference in restorative potential of nature and built environments depends on differences in the intrinsic characteristics of the stimuli. In addition, an evolutionary account is often assumed whereby restoration is believed to be a hardwired response to nature’s stimulus-features. Here, we propose the novel hypothesis tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 38 publications
6
44
1
2
Order By: Relevance
“…Importantly for the conceptual–organization hypothesis , relatively simple changes to the experiment, in which participants had to classify these difficult‐to‐identify and ambiguous sounds as natural or urban prior to aesthetically rating the sounds, was sufficient to shift the way in which aesthetic responses related to acoustic features of the sounds. These findings are conceptually similar to a recent study (Haga, Halin, Holmgren, & Sörqvist, ) demonstrating that an ambiguous noise was rated higher on restorative potential if participants were told it came from a waterfall (as opposed to urban machinery or no label). While Haga and colleagues demonstrate that an identical sound can be heard as either natural or urban, which then has implications for how the sound is evaluated, the present set of experiments expand upon these findings in at least two critical ways.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly for the conceptual–organization hypothesis , relatively simple changes to the experiment, in which participants had to classify these difficult‐to‐identify and ambiguous sounds as natural or urban prior to aesthetically rating the sounds, was sufficient to shift the way in which aesthetic responses related to acoustic features of the sounds. These findings are conceptually similar to a recent study (Haga, Halin, Holmgren, & Sörqvist, ) demonstrating that an ambiguous noise was rated higher on restorative potential if participants were told it came from a waterfall (as opposed to urban machinery or no label). While Haga and colleagues demonstrate that an identical sound can be heard as either natural or urban, which then has implications for how the sound is evaluated, the present set of experiments expand upon these findings in at least two critical ways.…”
Section: Discussionsupporting
confidence: 88%
“…This result further promotes the idea that at any point in time, the restorative value of nature experiences emerges from relationships among mind, body, and environment. This relational interpretation is in line with existing literature that suggests that the psychological effect of an experience is not a direct consequence of the stimuli per se, but of the meanings that are attributed to the stimuli [28]. In relational terms, regenerative compatibility actualises restoration in nature experiences.…”
Section: Regenerative Compatibilitysupporting
confidence: 86%
“…Evidence on restorative experiences has shown that urban natural areas have greater restorative effects on people than in built settings [4,[22][23][24]. This is true even when nature interactions happen at home and workspaces [25], just as 40-second views of green roofs [26], or through technological mediums [27], sounds [28,29] or printed photographs [30]. The urban green infrastructure has undoubtedly shown the potential to restore human health and wellbeing [2] and it is now considered a risk-decreasing solution for psychological and physiological disorders [31,32] Most of this research relies on the sole presence of natural features to explain the restorative effects of an environment.…”
Section: Aim and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem is that those sounds may not be easily separated from some technical sounds. For instance, Haga et al (2016) showed that participants perceived an ambiguous sound consisting of pink noise with white noise interspersed either as a nature sound (waterfall) or as an industrial sound in accordance with instructions given prior to the experiment.…”
Section: Discussionmentioning
confidence: 99%